2015
DOI: 10.1155/2015/537560
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Glycosaminoglycans/Proteoglycans as Carriers for Targeted Therapy Delivery

Abstract: The outcome of patients with cancer has improved significantly in the past decade with the incorporation of drugs targeting cell surface adhesive receptors, receptor tyrosine kinases, and modulation of several molecules of extracellular matrices (ECMs), the complex composite of collagens, glycoproteins, proteoglycans, and glycosaminoglycans that dictates tissue architecture. Cancer tissue invasive processes progress by various oncogenic strategies, including interfering with ECM molecules and their interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 256 publications
0
13
0
Order By: Relevance
“…Therapies that target the ECM provide a promising approach to overcome chemoresistance either by preventing ECM-conferred chemoresistance or by altering the ECM such that current therapies can overcome physical treatment limits [ 200 , 201 , 202 , 203 , 204 ]. It has been shown that the dense ECM can inhibit therapeutic drug penetration, diffusion and transport, thus the ECM acts as a barrier to drug delivery [ 205 , 206 , 207 , 208 , 209 , 210 , 211 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therapies that target the ECM provide a promising approach to overcome chemoresistance either by preventing ECM-conferred chemoresistance or by altering the ECM such that current therapies can overcome physical treatment limits [ 200 , 201 , 202 , 203 , 204 ]. It has been shown that the dense ECM can inhibit therapeutic drug penetration, diffusion and transport, thus the ECM acts as a barrier to drug delivery [ 205 , 206 , 207 , 208 , 209 , 210 , 211 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of PGs contain both O ‐ and N ‐type of glycans; however, as the O ‐glycan chain(s), called GAGs are much larger, representing more than a half of the PG MW, the properties and the biological activities of PGs are basically given by GAGs. Due to these carbohydrate chains, often hybrid, PGs are involved in various cellular signaling processes , and interact with many protein enzymes and growth factors (GFs). Minor changes into the fine structure of GAGs, which occur during the physiological process of maturation and aging, may trigger a series of biological events among which also the occurrence of cancer .…”
Section: General Considerations On the Structure And Functions Of Gagsmentioning
confidence: 99%
“…GAGs interact electrostatically with different compounds or biologics used for therapeutic purposes thanks to their strong negative charge. The drugs are delivered systemically or locally to treat a variety of pathological conditions, including cancer, glaucoma, wounds, and burns ( Misra et al, 2015 ).…”
Section: Glycosaminoglycans As Therapeutic Targetsmentioning
confidence: 99%